XUDOJNIK QUTTÍBEK JAQÍP DÓRETIWShILIGI - Eralin, Q.E.; Darmenov, J.A. (SCIENCE and SOCIETY, 2021)
The article reveals a number of aspects of the artist Kuttybek Zhakupov's work on the artistic processing of leather. The methods of creating panels made of leather with the use of methods: double-sided fur, cutting fur wool, using the texture of the skin for the composition are disclosed. The methods of creating a composition with the image of the front part of the skin, resembling the shape of the image in real life, are considered. Depending on the length, the wavy direction of the fur, the nature of the color, are defined as new means of composition. Rationally using the similarity of the manifestations of natural figurative forms on the surface of the skin with the manifestations of form in life, he revealed the idea of creation. A conceptual, narratological analysis of the artistic features of the panels made of leather is made.